Europe under Pressure The Development of the European Union under the Influence of the Arab Spring, the Refugee Crisis and the Global Threat of Terrorism - Dankert, Angelika C. (Tectum Wissenschaftsverlag, 2017)
The past years were characterized by a massive influx of migrants crossing the Union's external borders seeking asylum. Illegal migration, exploitation of social welfare systems, foreign infiltration and the instrumentalization of religion condensed in terror attacks determine today's changed attitude towards foreigners, refugees and migrants and therefore strongly impact the current European political agenda. Angelika C. Dankert describes the development of the EU and provides information on events that led to the creation and the spill-over of the Arab Spring. Roots and origin of Jihadist ideology as well as goals of religiously motivated terrorism are illustrated and European standards on morals and values are critically questioned. Through investigation of current matters in the field of law, security and interculturality, this book reveals the biggest geopolitical challenge of the 21st century.